A DNA-binding factor specific for xenobiotic responsive elements of P-450c gene exists as a cryptic form in cytoplasm: its possible translocation to nucleus. - Fujisawa-Sehara, A (1988)
Transcription of the drug-metabolizing cytochrome P-450c gene is induced by 3-methylcholanthrene or 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Previously, we defined two xenobiotic responsive elements (XREs) of approximately equal to 15 base pairs, both of which activate transcription in cis in response to these xenobiotics. Using a gel mobility shift assay, we have identified a factor that specifically binds to the XREs. This factor appears in nuclei of mouse hepatoma cell line Hepa-1 only when the cells are treated with the xenobiotics, while the factor is undetectable in the nuclei of a 3-methylcholanthrene-treated mutant of Hepa-1 with defective function of a xenobiotic receptor. In addition, the nuclear factor bound to the XRE in the gel was found to be associated with [3H]TCDD when the cells were treated with it, suggesting that the xenobiotic receptor is at least a component of the DNA-binding factor. The cytoplasmic fraction from nontreated Hepa-1 cells also contains the factor as a cryptic form and prominently reveals its DNA-binding activity by incubation with 3-methylcholanthrene in vitro. These results not only suggest the involvement of the XRE-binding factor in transcriptional activation via XREs but also provide evidence that the binding of ligands to the preexisting factor in a cryptic form induces its XRE-binding activity, which is probably followed by its translocation from cytoplasm to nucleus.